ANALYSING THE EFFECTIVENESS OF GUIDANCE AND COUNSELLING PLANNING MANAGEMENT IN THE DIGITAL ERA - Meifiana, Neha Eka; Sastranegara, Herlangsakati; Khusnah, Anik Asmaul; Christiana, Elisabeth (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to analyze the effectiveness of guidance and counseling planning management in the digital era in improving the quality of services that are responsive to student's needs as well as addressing the technical and ethical challenges that arise. Using a literature review approach, this study collected, analyzed, and synthesized various relevant literature sources related to the use of technology in guidance and counseling services. The results show that digital technology enables wider access, efficiency in data management, and flexibility in service delivery. However, challenges such as the digital divide, data security, and counselor competence in using technology are still obstacles. Therefore, careful planning, training for counselors, and strengthening regulations related to data privacy are needed so that guidance and counseling services can be more effective and responsive in the digital era.